Réponses

2013-09-24T16:09:06+02:00
4(2x-3)+x= 6+3(5x-1)
= 8x -12 +x = 6 +15x -3
= 8x +x -15x = 6 -3 +12
9x -15x = 18 -3
= -6x = 15
x = - 15/6

 (2x-3) (-5x+6) - (3x-1) (3-x)   

= (-10x² +12x +15x -18) - (9x -3x² -3+x)
= -10x² +27- 18 - 9x +3x² +3 -x
= -7x² +17x -15
2013-09-24T16:11:15+02:00
Résolution d'équations

4(2x-3) + x = 6 + 3 ( 5x -1)
8x -12 +x = 6 +15x -3
9x -15x = +12 +6 -3
-6x = +15
x = 15/6 

(2x-3)(-5x+6) -(3x-1)(3-x)               
-10x² +12x +15 x-18 -( 9x-3x² -3 +x)
-10x² +27x -18 -(10x -3x² -3)
-10x² +27x -18 -10x +3x² +3
-7x² +17x -15